The art of social media : power tips for power users - Kawasaki, Guy, 1954- (Portfolio/Penguin, 2014)
"A bottom-up strategy [intended] to produce a focused, thorough, and compelling presence on the most popular social-media platforms ... [guiding] you through steps to build your foundation, amass your digital assets, optimize your profile, attract more followers, and effectively integrate social media and blogging"--Amazon.com.